2018
DOI: 10.3390/md16080254
|View full text |Cite
|
Sign up to set email alerts
|

Absorption Study of Mozuku Fucoidan in Japanese Volunteers

Abstract: We performed an oral administration study of fucoidan in 396 Japanese volunteers and investigated significant factors concerning the absorption of fucoidan. Urine samples were collected at 0, 3, 6, and 9 h after ingestion of 3 g of fucoidan. Fucoidan was detected in urine after ingestion in 385 out of 396 subjects. The maximum value (mean ± standard deviation (SD)) of urinary fucoidan was 332.3 ± 357.6 μg/gCr in subjects living in Okinawa prefecture, compared with 240.1 ± 302.4 μg/gCr in subjects living outsid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 29 publications
(35 reference statements)
1
32
2
Order By: Relevance
“…Because H. pylori can induce drastic alterations in the variety of the gastrointestinal microbiota [29][30][31], the microbe is speculated to increase basal fucoidan levels by modifying the gastrointestinal microbiota. Basal fucoidan levels were also significantly higher in H. pylori-negative subjects who regularly consumed mozuku than in their counterparts who rarely ate mozuku, which confirmed our previous findings [13]. We speculated that Japanese people may have acquired digestive enzymes from mozuku because the seaweed is extensively consumed within this area.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Because H. pylori can induce drastic alterations in the variety of the gastrointestinal microbiota [29][30][31], the microbe is speculated to increase basal fucoidan levels by modifying the gastrointestinal microbiota. Basal fucoidan levels were also significantly higher in H. pylori-negative subjects who regularly consumed mozuku than in their counterparts who rarely ate mozuku, which confirmed our previous findings [13]. We speculated that Japanese people may have acquired digestive enzymes from mozuku because the seaweed is extensively consumed within this area.…”
Section: Discussionsupporting
confidence: 89%
“…A disadvantage of this test is that proteinuria can cause false-positive results; therefore, urine protein levels should be measured in future research. We plan to study the relationship of H. pylori infection with fucoidan absorption using serum-based ELISA kits or the 13 C urea breath test ( 13 C-UBT) in future research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, an oral administration and absorption study of Mozuku fucoidan in 396 Japanese volunteers was performed. Using multiple regression analyses, the significant factors influencing the absorption of fucoidan in the tested urine samples were investigated [104]. The results showed that fucoidan absorption in humans is extremely low; the fucoidan concentration after oral administration was approximately ten times higher in urine than in serum, confirming the intestinal absorption of Mozuku fucoidan in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, it has been reported that fucoidan is involved in immune activities, such as those of macrophages, NK cells, and cytokines [23,24]. Fucoidan derived from Okinawa mozuku has been confirmed to be absorbed by rodents and humans [25,26,27]. In this study, fucoidan was shown to be active in spleen immune cells, and macrophages in mice.…”
Section: Discussionmentioning
confidence: 54%